Free Trade Zones in Colombia: Business and Regional Development 2009 - 2016 - Arévalo-Luna, Guillermo Alexander; Arevalo-Lizarazo, Guillermo Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Free trade zones are an instrument of commercial policy that generates employment, investment and exports, thanks to tax incentives received by companies located into them. The objective of this paper is to examine the extent to which free trade zones policy during 2009 to 2016 contributed to concentrate production factors and polarized growth in central regions, while increasing regional disparity, given diverse characteristics of geographical character and factor endowment in the regions. The study uses the analytical-descriptive method from public and private statistical sources. The proposed hypothesis is: although free trade zones provide employment, increase investment and exports, they also intensify regional disparity. The study concludes that complementary public policies to the Free Trade Zones Law will have to attenuate territorial inequalities in favor of peripheral regions with higher relative backwardness.